2018
DOI: 10.1080/14760584.2018.1473765
|View full text |Cite
|
Sign up to set email alerts
|

Post-exposure prophylaxis (PEP) for rabies with purified chick embryo cell vaccine: a systematic literature review and meta-analysis

Abstract: Fifteen million people each year receive post-exposure prophylaxis (PEP) to prevent rabies, yet the disease remains neglected and highly under-reported. Areas covered: In this systematic literature review, we assessed the immunogenicity, efficacy, and safety of a purified chick embryo cell-culture rabies vaccine (PCECV) for PEP against rabies by intramuscular (IM) or intradermal (ID) administration. We performed meta-analyses to compare immunogenicity according to the route of vaccine administration, study pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…These initial two efficacy studies provided the proof needed that ID PEP was as effective as IM PEP when administered according to the schedules listed above and have served as models for designing additional clinical trials evaluating the effectiveness of new PEP regimens. Further clinical studies have confirmed that the other WHO prequalified rabies vaccines were also safe and effective for both IM PEP and ID PEP [ 10 , 13 , 24 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Comparing the Datamentioning
confidence: 97%
“…These initial two efficacy studies provided the proof needed that ID PEP was as effective as IM PEP when administered according to the schedules listed above and have served as models for designing additional clinical trials evaluating the effectiveness of new PEP regimens. Further clinical studies have confirmed that the other WHO prequalified rabies vaccines were also safe and effective for both IM PEP and ID PEP [ 10 , 13 , 24 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Comparing the Datamentioning
confidence: 97%
“…In our study, nearly all participants reported complete neutralization (ACIP criteria at the time of study preparation) at all time points post-vaccination. However, comparisons with earlier clinical studies of rabies vaccines are difficult due to a trend toward slightly decreased RVNA titers observed in recent studies for licensed rabies vaccines [ 34 ]. The reasons for the observed lower RVNA titers in more recent studies are likely multifactorial and may include varying definitions of the neutralization or seroconversion thresholds, HRIG interference, and variability of the RFFIT among different laboratories due to lack of standardization or differences in references used.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is the most effective and cost-efficient way to prevent the transmission of the virus. In addition to the traditional chicken embryo culture method for vaccine production, cell culture techniques are increasingly being employed, such as Vero cells for the production of COVID-19 vaccines ( Zhang et al, 2022 ), purified chick embryo cell-culture for rabies vaccines (PCECV; Preiss et al, 2018 ), and PER.C6 cells for the production of poliovirus vaccines ( Sanders et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%